The Influence of Audit Company Size, Asset Structure, Sales Growth, Profitability, On Capital Structure in the Tecnology Sector Listed on The Indonesian Stock Exchange (BEI) - Pera Hotriani Saragih; Enda Noviyanti Simorangkir; Beny Matthew Hasibuan; Rut Ningsih Sahanaya Manurung; Lainatu Shifa Rambe; Fhikry Ahmad Halomoan Siregar (International Journal of Economics, Management and Accounting (IJEMA), 2024)
This research aims to determine the influence of company size, asset structure, sales growth, profitability, on capital structure in the technology sector listed on the IDX. The population used in this research in technology sector companies listed on the IDX in 2020-2022. The method used in this research is a quantitave method. Samples taken using purposive sampling. The analysis technique used is classical assumption testing, hypothesis, multiple linear regression. This research uses data in the form of annual financial reports from each sample company which are published on the website www.idx.co.id. So, the number of samples in this study was 33 research samples. The results of this research show that company size, asset structure, sales growth, profitability have no effect and are not significant of capital structure.